PREPARING STUDENTS FOR AN EXPERIMENTAL TOUR ON QUALITATIVE DETERMINATION OF SUBSTANCES - Arkulova, D.; Zhanalinova, S. (PUBLISHINGS of Kostanay State Pedagogical Institute, 2020)
Currently, there are no works that contain the results of research on the methodological support of students in the Olympiad movement in chemistry, aimed at the development of thinking, which would reflect the system of work of the student in preparing students for the Olympics. A universal methodological system is needed to help students prepare for the experimental rounds of chemistry Olympiads. The process should be educational, targeting students in more sophisticated thinking.
Keywords: experimental round; a thought experiment; the matrix table